2017
DOI: 10.1007/s12274-017-1636-x
|View full text |Cite
|
Sign up to set email alerts
|

High-yield synthesis and liquid-exfoliation of two-dimensional belt-like hafnium disulphide

Abstract: Material synthesis and characterizationABSTRACT Producing monolayers and few-layers in high yield with environment-stability is still a challenge in hafnium disulphide (HfS 2 ), which is a layered two-dimensional material of group-IV transition metal dichalcogenides, to reveal its unlocked electronic and optoelectronic applications. For the first time, to the best of our knowledge, we demonstrate a simple and cost-effective method to grow layered belt-like nano-crystals of HfS 2 with surprisingly large interla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…Some computational and experimental results have demonstrated that NMP, IPA, and N ‐cyclohexyl‐2‐pyrrolidone (CHP) can form solvation shells on the surface of the nanosheets to inhibit surface degradation due to water and oxygen . Srivastava and co‐workers employed CHP, which belongs in the group of amide solvents, as the solvent to exfoliate HfS 2 under ambient conditions. These results revealed that exfoliation in CHP can prepare few‐layer and monolayer HfS 2 belts with a high yield, while the degradation of the obtained sheets is effectively prevented.…”
Section: Synthesismentioning
confidence: 99%
“…Some computational and experimental results have demonstrated that NMP, IPA, and N ‐cyclohexyl‐2‐pyrrolidone (CHP) can form solvation shells on the surface of the nanosheets to inhibit surface degradation due to water and oxygen . Srivastava and co‐workers employed CHP, which belongs in the group of amide solvents, as the solvent to exfoliate HfS 2 under ambient conditions. These results revealed that exfoliation in CHP can prepare few‐layer and monolayer HfS 2 belts with a high yield, while the degradation of the obtained sheets is effectively prevented.…”
Section: Synthesismentioning
confidence: 99%
“…In order to successfully extend the usage of these materials from laboratory to real-life applications, large scale and cost-effective production methods are required. During the past years, several bottom-up [14,[19][20][21][22][23][24][25][26][27][28] and top-down [29][30][31][32][33][34][35] strategies for the fabrication of atomically thin films have been developed. As has already been proven in the case of graphene, chemical vapour deposition (CVD) method is compatible with industry providing large area high quality material suitable for optoelectronic applications [36].…”
Section: Introductionmentioning
confidence: 99%
“…Zr x Hf 1-x S 2 : (a) [55] On (a): In addition to substitutions in anion sub-lattices, doping or substitutions on the cation positions are also investigated. [55] HfS 2 : (a) [14][15][16]18,30,56,57] On (a): HfS 2 can be obtained in crystalline form by chemical transport with the halogens Cl 2 , Br 2 , and I 2 as well as ICl 3 in a temperature gradient around 1000°C. Thin, extrafoliated crystals were investigated for their electrical properties.…”
Section: Groupmentioning
confidence: 99%
“…Thin, extrafoliated crystals were investigated for their electrical properties. [57] HfSe 2 : (a) [14,16,30,58] On (a): HfSe 2 can also be prepared in crystalline form by chemical transport. Iodine is described as a transport additive.…”
Section: Groupmentioning
confidence: 99%